DINAMIKA KOMUNIKASI ORGANISASI MASYARAKAT MARJINAL (Studi Pada Komunitas Perempuan Pekerja Seks Yogyakarta) - ERWIN RASYID (Jurnal Komunikasi, 2018)
Prostitution is sexual service for gaining cash. For someone who works in sexual service named as a prostitute or in Bahasa called as Pekerja Seks Komersial (PSK).  Nowaday PSK term constructed by people to discriminate the sex labor. Sometimes Perempuan pekerja seks (PPS) obtain the negative streotype from society, because they know as a moral offender in social culture. The term commercial sex worker or “PSK” in Indonesia is one example of a form of community discrimination born of  discourse formed by the mass media to women who work as a sex worker. In Special Region of  Yogyakarta (DIY) there are some areas that are often the place where sex workers peddle. Namely Pasar Kembang area or better known as sarkem, the Tugu railway station (Ngebong) and in the Giwangans Terminal. In the three areas there are three communities that become a forum for organizing PPS, among others Bunga Seroja community in Sarkem, Arum Dalu Sehat community in Ngebong and Surti Berdaya community in Giwangan. The three communities are under the umbrella of an organization called Perhimpunan Perempuan Pekerja Seks Yogyakarta (P3SY) in Indonesia. This paper aims to analyze what kind of development communication system that attempted to be constructed by female sex workers in Yogyakarta. The method used is descriptive qualitative.